PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA KEBERAGAMAN INDONESIA (UTAGASIA) UNTUK PEMBELAJARAN PPKN DI KELAS V SEKOLAH DASAR - Suci Andini; Munjiatun; Eddy Noviana (STKIP Subang, 2025)
The use of learning media in the teaching and learning process is important to increase the effectiveness and involvement of students in understanding the material. One of the learning media that can be used in learning Civics in grade V is the learning media of Indonesian diversity snakes and ladders (utagasia). This research aims to develop a valid and practical learning media of Indonesian diversity snakes and ladders (utagasia) in elementary schools. This media was developed using the R&D research method with the 4D model. Research data were collected by means of observation, interviews, and distributing questionnaires. Product validation was carried out by two experts, namely media experts and material experts with an overall average score of 88.01% with a very valid category. The results of product trials conducted on 16 students obtained an overall average score of 90.43% with a very practical category and a teacher response of 95% with a very practical category. Based on the results of validation and trials, it can be concluded that the learning media of Indonesian diversity snakes and ladders (utagasia) is suitable for use in learning.